PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA - Warih Nurul Hidayati; Joko Subando (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
In the educational process implemented in learning activities, it is influenced by a very important component, namely the curriculum. The curriculum is a description of a number of learning materials or lesson materials, learning objectives, and guidelines for teachers in preparing the syllabus. Madrasah is formal education that is rich in Islamic educational material. Madrasas equip their students with religious knowledge. Have knowledge and religious character. By instilling the values ​​of Islamic teachings, the role of madrasas is to equip students with knowledge that suits their future life needs and to become a forum for the formation of religious character so that they become knowledgeable human beings who always carry their commands with them.